Leveraging External Networks and Internal Capabilities: A Pathway to Innovation in an Export Economy - Boonchoo, Pattana; Thoumrungroje, Amonrat; Racela, Olimpia C. (Ital Publication, 2025)
Objectives: This study examines the role of business network ties, financial resource accessibility, and export market-oriented capability in influencing product innovation intensity in Myanmar’s transitional economy. Grounded in social network theory and resource-advantage theory, it explores how firms leverage external networks and internal capabilities to foster innovation despite economic and institutional constraints. Methods/Analysis: Survey data were collected from 161 Myanmar exporters representing various industries. Structural equation modeling (SEM) was employed to test the hypothesized relationships. Findings: The results confirm that business network ties significantly enhance financial resource accessibility, with quantity, proximity, and frequency all playing critical roles. Financial resource accessibility exerts a greater influence on innovation than market-oriented capability, highlighting their instrumental role. Exporters should prioritize strategic network development to enhance financial resource access. Policymakers should facilitate business networking, financial accessibility, and export support programs to promote sustainable innovation-driven growth. Novelty/Improvement: This study fills a critical literature gap by empirically linking business network ties, financial resource acquisition, market-orientation, and innovation in a transitional economy, offering rare insights for exporters striving in resource-constrained environments. Future research should explore network dynamics, resource access, market orientation, and innovation in various transitional economies to improve generalizability.